2022
DOI: 10.33448/rsd-v11i1.24908
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and seasonal variation of the volatile oils from Siparuna guianensis Aubl. leaves collected from Monte do Carmo, Tocantins

Abstract: Siparuna guianensis Aubl., known as “negramina”, “capitu”, is a small tree used for headaches, colds, fevers, as a healing agent, insect, and tick repellents. This study aimed to evaluate the chemical composition and seasonal variability of essential oils from the leaves of S. guianensis. Botanical material was collected in Monte do Carmo, Tocantins, Brazil. The powder from the leaves was submitted to hydrodistillation in a Clevenger apparatus, and the identification of the compounds was performed by GC-MS. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…In general, S. guianensis EO has a predominance of sesquiterpenes, followed by oxygenated sesquiterpenes and, to a lesser extent, monoterpenes, which is consistent with observations of Diniz et al (2022), Souza et al (2022), and others, who identified them as the main constituents of the volatile oils from S. guianensis leaves collected in Zona da Mata, Minas Gerais; Cantá, Roraima state; and Monte do Carmo, Tocantins, in Brazil.…”
Section: Gc-ms Analysis and Identification Of Components Of S Guianen...supporting
confidence: 88%
See 1 more Smart Citation
“…In general, S. guianensis EO has a predominance of sesquiterpenes, followed by oxygenated sesquiterpenes and, to a lesser extent, monoterpenes, which is consistent with observations of Diniz et al (2022), Souza et al (2022), and others, who identified them as the main constituents of the volatile oils from S. guianensis leaves collected in Zona da Mata, Minas Gerais; Cantá, Roraima state; and Monte do Carmo, Tocantins, in Brazil.…”
Section: Gc-ms Analysis and Identification Of Components Of S Guianen...supporting
confidence: 88%
“…The biosynthesis of EO occurs in aromatic plants through enzymatic reactions and can be present in leaves, roots, seeds, stems, flowers, and fruits (Rehman et al, 2016), whose liquid volatile compounds are responsible for plant aromas. One family of aromatic and medicinal plants is Siparunaceae (de Souza et al, 2022;Silva et al, 2021;Lourenço et al, 2018), which consists of two genera: Glossocalyx and Siparuna, both of which produce EO. The species Siparuna guianensis Aublet stands out within the Siparunaceae family, whose quantification of the components of the essential oil has already been reported (Diniz et al, 2022;Souza et al, 2022), as well as its various uses as insecticide and repellent (Ferreira et al, 2019;Toledo et al, 2019;Lourenço et al, 2018), and its acaricidal (Diniz et al, 2022), pharmacological (anthelmintic, anti-inflammatory, antinociceptive, anticariogenic, antimycobacterial activities) and antifungal properties (Conegundes et al, 2021;Silva et al, 2021;Santos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…También se ha evaluado la actividad antimicrobiana de los AEs obtenidos de las hojas de S. macrotepala y S. aspera (Noriega et al, 2019). Los componentes mayoritarios identificados en el aceite esencial de S. guianensis son γ-muuroleno (13.99 a 35.97%, curzereno (7.22 a 19.15%, curzerenona (7.3 a 18.13%) y 2-undecanona (3.99 a 10.63% (De souza et al,2022); destacándose entre estos la 2undecanona conocida por poseer propiedades repelentes sobre mosquitos vectores de enfermedades (Andrade-Ochoa et al, 2017).…”
Section: Estos Extractos Han Sido Ampliamente Estudiadosunclassified